Generation of Bessel vortex beams in the subterahertz range using reflecting diffractive optical elements - V.V. Gerasimov; N.D. Osintseva; V.S. Pavelyev; A.N. Agafonov (Компьютерная оптика)
In this work, we propose a simple method for generating Bessel vortex beams in the subterahertz (subTHz) range with the orbital angular momentum with l = 1 based on reflecting metal diffractive optical elements with a continuous helical microrelief. The elements are fabricated by micromilling in a polished duralumin substrate and by tin casting, and tested using a backward wave oscillator (wavelength λ = 855 µm). When using the micromilled element, Bessel vortex beams are shown to be generated and retain a Bessel intensity profile at a distance of 20–50 mm from the reflecting element, which is in good agreement with the results of numerical simulation. An experimental estimate of the energy efficiency of this element is 63%. When using elements made by tin casting, the vortex beams are generated with a distorted profile due to the presence of residual deformations of tin, which has plasticity. Due to their high conductivity, metallic reflecting elements can be used with high power density sub-THz radiation sources such as free electron lasers and gyrotrons.